Rehearsal grouping of liver disease, during an observation of hepatic visceral tertiarism - Odriozola, Ernesto (1918)
You know the patient occupied bed No. 32 in our room. It is not, in this case, an extraordinary indeed sick; but their knowledge is very useful, because the purpose of the chair of clinic here and elsewhere, should be to study the common sick, ie those with whom we have to stumble daily and constitute therefore, the main element of ordinary practice, doctors must know thoroughly and in detail.